Surface science experiments involving the atomic force microscope - McBride, Sean P. (Kansas State University, 2012)
Three diverse first author surfaces science experiments conducted by Sean P. McBride 1-3 will be discussed in detail and supplemented by secondary co-author projects by Sean P. McBride, 4-7 all of which rely heavily on the use of an atomic force microscope (AFM). First, the slip length parameter, b of liquids is investigated using colloidal probe AFM. The slip length describes how easily a fluid flows over an interface. The slip length, with its exact origin unknown and dependencies not overwhelming decided upon by the scientific community, remains a controversial topic. Colloidal probe AFM uses a spherical probe attached to a standard AFM imaging tip driven through a liquid. With the force on this colloidal AFM probe known, and using the simplest homologous series of test liquids, many of the suspected causes and dependencies of the slip length demonstrated in the literature can be suppressed or eliminated. This leaves the measurable trends in the slip length attributed only to the systematically varying physical properties of the different liquids. When conducting these experiments, it was realized that the spring constant, k, of the system depends upon the cantilever geometry of the experiment and therefore should be measured in-situ. This means that the k calibration needs to be performed in the same viscous liquid in which the slip experiments are performed. Current in-situ calibrations in viscous fluids are very limited, thus a new in-situ k calibration method was developed for use in viscous fluids. This new method is based upon the residuals, namely, the difference between experimental force-distance data and Vinogradova slip theory. Next, the AFM’s ability to acquire accurate sub nanometer height profiles of structures on interfaces was used to develop a novel experimental technique to measure the line tension parameter, τ, of isolated nanoparticles at the three phase interface in a solid-liquid-vapor system. The τ parameter is a result of excess energy caused by the imbalance of the complex intermolecular forces experienced at the three phase contact line. Many differences in the sign and magnitude of the τ parameter exist in the current literature, resulting in τ being a controversial topic.
Keywords: Line tension; Surface science; Slip length; Atomic force microscope (AFM); Colloidal probe AFM; Residuals calibration; Condensed Matter Physics (0611); Nanoscience (0565); Physics (0605)